Nitrogen isotope exchange between NO and NO2 and its implications for δ15N variations in tropospheric NOx and atmospheric nitrate. Issue 1 (6th January 2016) - Walters, Wendell W.; Simonini, Damian S.; Michalski, Greg
Abstract: The nitrogen (N) isotope exchange between nitric oxide (NO) and nitrogen dioxide (NO2 ) has been previously suggested to influence N stable isotope compositions ( δ 15 N) of these molecules. However, there is disagreement in the magnitude of the N isotopic fractionation ( α NO 2 / NO ) resulting from this exchange process between previous experimental and theoretical studies. To this end, we measured α NO 2 / NO associated with this exchange reaction at various temperatures. Our results indicate α NO 2 / NO to be 1.0403 ± 0.0015, 1.0356 ± 0.0015, and 1.0336 ± 0.0014 at 278 K, 297 K, and 310 K, respectively. These measured values are within experimental error of the values we calculated using a modified version of the Bigeleisen‐Mayer equation corrected for accurate zero‐point energies, indicating an agreement between experiment and theory. Modeling of this exchange reaction demonstrates that δ 15 N‐NO2 may exhibit a diurnal and seasonal profile if N isotopic equilibrium is achieved. Key Points: Nitrogen isotope exchange fractionation between NO and NO2 was measured Experimental measurements agree with theoretical calculated values Implications for δ 15 N variations in atmospheric NO2 and nitrate